THE USE OF HYBRID VEHICLES AS A PROPOSAL FOR REDUCING CO2 EMISSIONS AND ITS CONTRIBUTION TO REDUCING GREENHOUSE GAS EMISSIONS - de Carvalho, C. A. R.; Lamas, W. Q. (Revista de Engenharia Térmica, 2009)
The problems related to energy consumption and pollutant emissions for the transport sector represent a major global concern regarding climate changes caused by greenhouse gases, directly related to the increased level of gas emissions from fossil fuels , the main one being carbon dioxide. One way to minimize this problem is through the introduction of new technologies. Hybrid cars are one of the new technology options that has the main advantage of reducing fuel consumption and therefore reducing the amount of CO2 in the atmosphere. This paper gives an introduction to hybrid vehicles, with the aim of presenting their main advantages and evaluate their impact on emissions of CO2 in the Brazilian fleet, compared to conventional vehicles.